Permutation entropy applied to the characterization of the clinical evolution of epileptic patients under pharmacological treatment - Mateos, Diego; Díaz, Juan Manuel; Lamberti, Pedro Walter (2021)
Fil: Mateos, Diego. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.